Perioperative care of patients at high risk for stroke during or after non-cardiac, non-neurologic surgery: consensus statement from the Society for Neuroscience in Anesthesiology and Critical Care - Mashour, George A; Moore, Laurel E; Lele, Abhijit V; Robicsek, Steven A; Gelb, Adrian W (Journal of neurosurgical anesthesiology, 2014)
Perioperative stroke can be a catastrophic outcome for surgical patients and is associated with increased morbidity and mortality. This consensus statement from the Society for Neuroscience in Anesthesiology and Critical Care provides evidence-based recommendations and opinions regarding the preoperative, intraoperative, and postoperative care of patients at high risk for the complication.